Distinctive Binding of Three Antagonistic Peptides to the Ephrin-Binding Pocket of the EphA4 Receptor - Lamberto, Ilaria (2012)
The EphA4 receptor tyrosine kinase interacts with ephrin ligands to regulate many processes, ranging from axon guidance and nerve regeneration to cancer malignancy. Thus, antagonists that inhibit ephrin binding to EphA4 could be useful for a variety of research and therapeutic applications. Here we characterize the binding features of three antagonistic peptides (KYL, APY and VTM) that selectively target EphA4 among the Eph receptors. Isothermal titration calorimetry analysis demonstrates that all three peptides bind to the ephrin-binding domain of EphA4 with low micromolar affinity. Furthermore, the effects of a series of EphA4 mutations suggest that the peptides interact in different ways with the ephrin-binding pocket of EphA4. Chemical shifts observed by NMR spectroscopy upon binding of the KYL peptide involve many EphA4 residues, consistent with extensive interactions and possibly receptor conformational changes. Additionally, systematic replacement of each of the 12 amino acids of KYL and VTM identify the residues critical for EphA4 binding. The peptides exhibit a long half-life in cell culture medium, which with their substantial binding affinity and selectivity for EphA4 makes them excellent research tools to modulate EphA4 function.